HUBUNGAN PENGETAHUAN IBU DAN DUKUNGAN SUAMI TERHADAP PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS PAAL MERAH II KOTA JAMBI TAHUN 2026 - Silvia Mariana; Rani Hosiana Br Sinurat; Putri Lestari; Reni Hariyanti (Jurnal Kesehatan dan Pembangunan, 2026)
Exclusive breastfeeding is a method for improving child health. Exclusive breastfeeding rates remain far from ideal due to the influence of various factors, including maternal understanding and partner motivation. This study aims to investigate the relationship between maternal knowledge and husband support with exclusive breastfeeding at the Paal Merah II Community Health Center in Jambi City in 2026. This study is quantitative, using an analytical survey design with a cross-sectional approach. Chi-square analysis was applied to determine the relationship between variables, with a p-value less than 0.05 indicating a significant relationship. The population consisted of mothers currently breastfeeding their children over 6 months old, with a total of 45 respondents obtained through a total sampling technique. The results indicated that 33 respondents (73.3%) were exclusively breastfeeding. Regarding knowledge, 20 respondents (44.4%) had good knowledge, while 24 respondents (53.3%) had good husband support. The results of the statistical analysis showed that there was no significant relationship between maternal knowledge level and exclusive breastfeeding, with a p-value of 0.009. On the other hand, there was a significant relationship between husband's support and exclusive breastfeeding, with a p-value of 0.022. This study concluded that there was no significant relationship between mothers' knowledge levels regarding exclusive breastfeeding and no strong correlation between husband's support and exclusive breastfeeding at the Paal Merah II Community Health Center in Jambi City in 2026.